Knowledge, attitude and behaviour of farmers towards the use of reproductive hormones in dairy cattle - A. Wicaksono; W. Steeneveld; T. van Werven; H. Hogeveen; B.H.P van den Borne (Animal)
Reproductive hormones are regularly applied in dairy farms for cow fertility management regarding oestrus induction and treatment of reproductive diseases. The use of hormones in dairy farms needs to be explored with insight into the farmers’ knowledge and attitude to obtain their reasoning behind their behaviour of hormone use. This study aimed to determine and associate dairy farmers’ knowledge and attitude with their reproductive hormone use behaviour. An online questionnaire on reproductive hormone use was distributed by 15 veterinary practices, who distributed it to their dairy farm members through email or as an inclusion in an online newsletter. The questionnaire was responded by 188 farmers (response rate of 13%). Data on herd characteristics, knowledge, attitude and hormone use behaviour (self-reported based on a questionnaire and actual use based on hormone sales data) were collected. A knowledge score (0–10) was based on 10 objective knowledge questions. An explanatory factor analysis was conducted to identify latent structures among 19 attitude variables, resulting in four−factor variables. Several regression analyses were conducted to associate knowledge with attitude (multivariate multiple regression), knowledge and attitude with self-reported behaviour (logistic regression) and with actual hormone use (negative binomial regression). All models corrected for eight herd characteristic variables. The mean knowledge score was 5.9 ± 1.8 and 83% of the farmers indicated that they used hormones if their cows were not in oestrus after exceeding some expected days in milk. No significant association was found between knowledge and four attitude factors. However, a higher knowledge score was positively associated with hormone use behaviour (self-reported and actual hormone use). The same direction was shown for a stronger attitude on the benefits of using hormone with both higher hormone use behaviours. A stronger attitude on following the treatment protocol was positively associated with a higher actual hormone use while a stronger attitude towards non-hormonal fertility management was associated with a lower actual hormone use. In conclusion, determining farmers’ objective knowledge and attitude provided the reasoning behind their hormone use behaviour. Furthermore, obtained insights into knowledge, attitude and behaviour might therefore be beneficial for improving fertility guidelines.